A case of freestyle valve reoperation 23 years after the first operation. (July 2022) - Kawaida, Taiki; Tanabe, Hiroaki; Kato, Yuji; Yamazaki, Shintaro; Hosaka, Kimio; Toyama, Masaaki
We present a case of redo stentless valve operation in a 73-year-old man who underwent aortic valve replacement via the subcoronary approach with a freestyle aortic bioprosthesis 23 years ago at our institution. He was referred for surgery because an echocardiogram showed severe aortic regurgitation due to structural valve deterioration, and aortic valve replacement was planned. Severe circumferential calcification and adhesion were noted during the surgery between the freestyle and native roots. Redo-aortic valve replacement was successful despite the technical difficulty. In stentless valve reoperations following aortic valve replacement via the subcoronary method, the planning of valve-in-valve transcatheter aortic valve implantation and sutureless valve implantation may be a practical and safe strategy.